POSSIBILITIES OF ROAD CARRIAGE OF FIREWORKS IN SLOVAK REPUBLIC (Perner's Contacts, 2019)
This manuscript discusses the possibilities of road carriage of pyrotechnic articles and fireworks, which are labeled as dangerous goods, which means that they are covered by the European Agreement Concerning the International Carriage of Dangerous Goods by Road (ADR). In the manuscript fireworks are identified in the first chapter, while the second chapter describes the conditions for the consignor before the transport. The third part of the article points out the possibilities of influencing such transport.